Análise de observação do ensino da libras com L1 e L2. - Nascimento Junior, Osvaldo de Oliveira (Brasil, 2022)
The Supervised internship is the moment to gather all the theoretical knowledge built during four years in the Letras-Libras course; and see how this knowledge applies in real-life practice. This observation stage provided several reflections in the lives of future teachers in relation to different realities, situations that are present in the daily life of teaching Libras such as L1 and L2. The main focus of this work was to observe and analyze, through the internship experience, different methodologies in relation to the teaching of Libras; targeting the varied profile of teachers, different contexts and the relationship between student and teacher. Making a list of the points that were observed within the internship and joining with theoretical reflections that explain teaching and learning methodologies of Libras such as L1 and L2. The L1 internship took place in a single educational institution, Filippo Smaldone, while the L2 internship took place in three different institutions at DDPM, Escola Frei Silvio Vaghegg and UEA-ENS. Finally, enriching the internship experience, the conducting took place, where it was possible to put into practice activities related to teaching, adding current reflections on the teaching of Libras with L1 and L2.